Pharmacological basis of bergapten in gastrointestinal diseases focusing on H+/K+ ATPase and voltage-gated calcium channel inhibition: A toxicological evaluation on vital organs - Aslam, Huma; Khan, Arif-ullah; Qazi, Neelum Gul; Ali, Fawad; Hassan, Syed Shams ul; Bungau, Simona (Frontiers in Pharmacology, 2022)
This study aimed at establishing a pharmacological basis to evaluate the effects of bergapten (5-methoxypsoralen) in gastrointestinal diseases and assessment of its toxicological profile. The pharmacokinetic profile was evaluated using the SwissADME tool. Whereas AUTODOCK and PyRx were used for evaluating the binding affinities. The obtained results were further investigated for post-dock analysis using Discovery Studio Visualizer 2016. Desmond software package was used to conduct molecular dynamic simulations of best bound poses. Bergapten was further investigated for antidiarrheal, antisecretory, charcoal meal transit time, antiulcer, anti H.pylori activity. Bergapten at dose of 50, 100 and 200 mg/kg proved to effectively reduce diarrheal secretions, and reduced intestinal seretions, reduce distance moved by charcoal meal. Bergapten at above mentioned doses acts as gastroprotective agent in ethanol induced ulcer model that an be attributed to its effectiveness against H.pylori. Bergapten shows concentration-dependent relaxation of both spontaneous and K+ (80 mM)-induced contractions in isolated rabbit jejunum model, the Ca2+ concentration–response curves (CRCs) were shifted to the right showing potentiating effect similar to papaverine. For molecular investigation H+/K+-ATPase inhibitory assay indicated inhibition of pump comparable to omeprazole. Oxidative stress markers GST, GSH and Catalase showed increased expression whereas LPO’s expression was reduced. Histopathological examination indicated marked improvement in cellular morphology. ELISA and western blot confirmed the reduction in inflammatory mediator’s expression. RT-PCR reduced mRNA expression level of H+/K+-ATPase confirming inhibition of the pump. The toxicological profile of bergapten was evaluated by acute toxicity assay and evaluated for behavioral analysis and the vital organs were used to analyze the biochemical, hematological and histopathological examination. Bergapten at the tested doses proved to be an antioxidant, anti-inflammatory, antiulcer, antidiarrheal agent and relatively safe in acute toxicity assay.